A Study on Frictional Properties of Denim Fabric - Mohanbharathi, C.; Dileep Kumar, K.; Karthikeyan, V.; Manikandan, P. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This Project is focused on frictional behavior between the denim fabric and human skin. To study on the frictional relation between human skin and fabric by using denim fabric. Analyzing the frictional properties of denim fabric. Count, ends per inch, picks per inch blend of the denim fabric is tested. The friction in the fabric reduced by giving enzyme finish to the fabric that is given to the cellulase and alovera. Chemicals are not used for finishing.
Keywords: Denim; Desizing; Scouring and Friction